The literature of democracy - Harman, E. Hortensia (My University, 1895)
Introduction: The character of a people is written as indelibly on the pages of its literature as is the bounty of nature inscribed on her wonderful scroll of field, forest, and sea. In a study of writers, the real criterion is the inherent worth, the truth and soundness of the production and the perfection of its form. But this criterion is now seldom applied exclusively, the supreme test being associated in modern criticism with others of varying importance.
Citation: Harman, E. Hortensia. The literature of democracy. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Nature; Literature; People; Theses; Manuscripts (documents)